Two-Electron Reaction without Structural Phase Transition in Nanoporous Cathode Material - Tomoyuki Matsuda; Yutaka Moritomo (Journal of Nanotechnology)
We investigated the charge/discharge properties, valence states, and structural properties of a nanoporous cathode material LixMn[Fe(CN)6]0.83·3.5H2O. The film-type electrode of LixMn[Fe(CN)6]0.83·3.5H2O exhibited a high charge capacity (=128 mAh g-1) and a good cyclability (87% of the initial value after 100 cycles) and is one of the promising candidates for Li-ion battery cathode. X-ray absorption spectra near the Fe and Mn K-edges revealed that the charge/discharge process is a two-electron reaction; that is, MnII–NC–FeII, MnII–NC–FeIII, and MnIII–NC–FeIII. We further found that the crystal structure remains cubic throughout the charge/discharge process. The lattice constant slightly increased during the [FeII(CN)6]4-/[FeIII(CN)6]3- oxidization reaction while decreased during the MnII/MnIII oxidization reaction. The two-electron reaction without structural phase transition is responsible for the high charge capacity and the good cyclability.